Living Hadith in Sumbayang Ampek Puluah Tradition at Pandai Sikek, West Sumatra - Abdul Halim (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
Sumbayang Ampek Puluah or Forty Days Prayer is an annual tradition carried out by the congregation of Surau Gadang Haji Miskin, Koto Tinggi Pandai Sikek, West Sumatra. This paper examines the transmission lines and reasons for the Sumbayang Ampek Puluah tradition's existence and survival. This research studies living hadith using the phenomenological and sociological-knowledge approaches of Peter L. Berger. Field facts show that the Sumbayang Ampek Puluah tradition is carried out every 15th of the month of Sha'ban to the 25th of the month of Ramadan. This study found that there are three motivations for the congregation to implement this tradition, apart from the large reward (pahala) of the congregational prayer: (1) because of the large Sumbayang Ampek Puluah fadilah mentioned in the hadith, especially if the time of its implementation is in the month of Ramadan; (2) to preserve the traditions of the ancestors; (3) because other congregations influenced them. The benefits of this tradition are calm and peace of mind, discipline in worship, maintenance of kinship ties, and the growth of a high attitude of solidarity among fellow worshippers. Thus, they are determined to preserve and teach it to the next generation.